Advantages of robotic arm-assisted total hip arthroplasty: a 90-day episode-of-care clinical utility and cost analysis - Wael Barsoum; David Gregory; Keith Needham; Michael Mont; Nipun Sodhi; Andrea Coppolecchia; David Jacofsky (Becaris Publishing Limited, 2023)
Aim: Determine the clinical utility and economic differences over a 90-day period between robotic armassisted total hip arthroplasty (RATHA) and manual total hip arthroplasty (MTHA). Methods: Leveraging a nationwide commercial payer database, pre-covid THA procedures were identified. Following a 1:5 propensity score match, 1732 RATHA and 8660 MTHA patients were analyzed. Index costs, index lengths of-stay, and 90-day episode-of-care utilization and costs were evaluated. Results: Episode of care costs for RATHA was found to be $1573 lower comparedwithMTHA (p<0.0001). Post-index hospital utilization was significantly less likely to occur for RATHA compared with MTHA. Total index costs were also significantly lower for RATHA versusMTHA (p < 0.0001). Conclusion: Index and post-index EOC hospital utilization and costs were lower for RATHA compared with MTHA.